Model Partnerstwa Lokalnego w powiecie siedleckim - Kałuża, Halina (Local Partnership Model in Siedlce District, 2006)
From the meetings which have been held, it appears that entrepreneurs need mostly to get bussines and financial advice. They suggest setting up a firm incubator to help entrepreneurs to change a good idea into a new local firm. In May 2006 specific projects come into existence and they influence the development and boom in Siedlce and in Siedlce district.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 354-360